2014
DOI: 10.1007/s00464-014-3576-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and durability of robotic heller myotomy for achalasia: patient symptoms and satisfaction at long-term follow-up

Abstract: There is a dearth of long-term follow-up data to support the effectiveness of RHM. This study demonstrates durable dysphagia relief in the vast majority of patients with a high degree of patient satisfaction and a low rate of esophageal mucosal injury. While a significant proportion of patients report reflux symptoms, these symptoms are well controlled with medical acid suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
4
29
0
1
Order By: Relevance
“…35 Perry et al, evaluated the difference in medication use between MIS approaches, and found 56% of robotic patients and 80% of laparoscopic patients required medication for reflux at LT follow-up. 14 While they cite their PPI use as "very high," the authors point to a need for objective testing to determine if the symptoms are truly a result of acid reflux. Others have reported more descriptive breakdowns, with 41%, 7% and 2% of patients post-operatively taking PPIs, CCBs, and Nitroglycerine, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Perry et al, evaluated the difference in medication use between MIS approaches, and found 56% of robotic patients and 80% of laparoscopic patients required medication for reflux at LT follow-up. 14 While they cite their PPI use as "very high," the authors point to a need for objective testing to determine if the symptoms are truly a result of acid reflux. Others have reported more descriptive breakdowns, with 41%, 7% and 2% of patients post-operatively taking PPIs, CCBs, and Nitroglycerine, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Still, fewer authors have looked at robotic HM, with small cohorts ranging from 14-56 patients. 14,15 Therefore, despite the data that exist on MIS benefits for surgical procedures in general, there is a lack of research substantiating feasibility and LT results after both minimally invasive Heller approaches, especially those with a long follow-up time. Given the efficacy of minimally invasive approaches in other surgical fields, the aim of our study was to evaluate short and LT symptom improvement in patients who underwent MIHM.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, minimally invasive Heller myotomy is currently the gold standard surgical approach for achalasia as it has the best long-term outcome. Although per-oral endoscopic myotomy (POEM) and robotic Heller myotomy (RHM) are increasingly being used, laparoscopic Heller myotomy (LHM) is the longest practiced surgical approach with safe and effective outcomes [8,9,[12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…It was first described in 2001 in a case report by Melvin et al [16] . At this point, outcomes are somewhat controversial for RHM compared to LHM; however, many studies report that it is equivalent to LHM in terms of achieving the desired result of symptomatic relief but with fewer complications related to mucosal perforation [9,13,14,[17][18][19][20] . Cost remains one of the largest barriers to overcome in robotic operations; however, cost reduction strategies can be further explored with increased utilization [10,17,19,21] .…”
Section: Introductionmentioning
confidence: 99%
“…RAHM has equal efficacy to Laparoscopic Heller's myotomy (LMH) but lower rate of mucosal perforations. [1] Therefore, it is possible that more number of surgical myotomies may be robot assisted in the near future. However, RAHM is costlier in comparison to LHM.…”
mentioning
confidence: 99%